Collaborative Care to Improve Access and Quality in School‐Based Behavioral Health. (14th October 2019) - Lyon, Aaron R.; Whitaker, Kelly; Richardson, Laura P.; French, William P.; McCauley, Elizabeth
ABSTRACT: BACKGROUND: Collaborative care (CC) is a well‐established approach for the delivery of accessible behavioral health services in integrated health care settings. Substantial evidence supports its effectiveness in improving the quality and outcomes of adult services, and growing research indicates utility with child and adolescent populations. METHODS: To date, studies examining CC models for youth have focused exclusively on primary‐care settings. Nevertheless, as the most common integrated service delivery setting for youth, the education sector is an equally important context for improving access to behavioral health services for children and adolescents. RESULTS: We provide a narrative review of the literature on CC, describes the relevance of CC to schools, and details its alignment with contemporary movements in education and school‐based behavioral health. CONCLUSIONS: Potential adaptations of the CC model for use in schools are detailed to improve: (1) behavioral health service accessibility, (2) the capacity of schools to provide behavioral health services, and (3) school service effectiveness through use of evidence‐based practices. Although little research has explored the applicability of CC in the education sector, the model holds potential promise to improve the quality and efficiency of school‐based behavioral health services.